2013
DOI: 10.7250/msac.2013.005
|View full text |Cite
|
Sign up to set email alerts
|

Polyisoprene/Nanostructured Carbon Composites for Applications in Temperature Sensors

Abstract: Abstract. The studies of electrical properties of the polyisoprene (PI) matrix/high structure carbon black (HSCB) composites (PCBC) with various concentrations (8, 9, 10 and 11 mass parts) of filler have been carried out in the temperature interval of 90K-330K. In this paper we focus on the investigation of direct current (DC) conductivity in a low-temperature region with negative temperature coefficient of resistivity (NTCR). It has been proven that variable range hopping (VRH) conduction is dominated by hopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…30 Similar measurements on rGO-based nanocomposites have been conducted to reveal the dominant transport mechanism of those systems. Knite et al reported a crossover from Mott-VRH to nearest neighbor hopping (Arrhenius) on polyisoprene/nanostructured carbon composite at ∼230 K. 31 In a limited temperature range (300−373 K), Nagesh Kumar et al observed Mott 3D-VRH transport process in rGO-ZnO nanocomposite. 32 Song et al used parallel register model to represent the temperature dependence of resistivity across metal−insulator transition in a hexagonal boron nitride− graphene hybrid composite and reported ES-VRH as the dominant transport process only in the insulating region of temperature dependence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Similar measurements on rGO-based nanocomposites have been conducted to reveal the dominant transport mechanism of those systems. Knite et al reported a crossover from Mott-VRH to nearest neighbor hopping (Arrhenius) on polyisoprene/nanostructured carbon composite at ∼230 K. 31 In a limited temperature range (300−373 K), Nagesh Kumar et al observed Mott 3D-VRH transport process in rGO-ZnO nanocomposite. 32 Song et al used parallel register model to represent the temperature dependence of resistivity across metal−insulator transition in a hexagonal boron nitride− graphene hybrid composite and reported ES-VRH as the dominant transport process only in the insulating region of temperature dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Similar measurements on rGO-based nanocomposites have been conducted to reveal the dominant transport mechanism of those systems. Knite et al reported a crossover from Mott-VRH to nearest neighbor hopping (Arrhenius) on polyisoprene/nanostructured carbon composite at ∼230 K . In a limited temperature range (300–373 K), Nagesh Kumar et al observed Mott 3D-VRH transport process in rGO-ZnO nanocomposite .…”
Section: Introductionmentioning
confidence: 99%